Fostering Students' Cognitive Abilities Using Teams Games Tournament (TGT): An Action Research - Fussalam, Yahfenel Evi; Silvia, Resi; Rahmawati, Sophia; Sartika, Dani; Aprillitzavivayarti, Aprillitzavivayarti; Marlina, Leni (Indonesian Research Journal in Education |IRJE|, 2023)
The research was conducted as a potential means to address the issues about low student learning outcomes, especially in cognitive abilities. Facts show that the score was still below the minimum mastery criteria of 75, especially in the field of social science for sixth-grade students. Social studies learning is recorded as it still uses conventional methods and teachers rarely give feedback on student work, coupled with the minimal use of media and not providing motivation to students. The present research aimed to apply the teams’ games tournament (TGT) approach to enhance the students’ cognitive abilities. The researchers employed two improvement cycles in the form of classroom action research procedures. The progress of students' learning outcomes was in each cycle, starting at 34.62% in the pre-cycle, completeness rose to 84.6% after the first cycle and reached 92.3% in the second cycle. The research results suggest that the implementation of the TGT method yielded a significant improvement in cognitive abilities of academic achievement among the research participants.